2015
DOI: 10.1007/s10067-015-2881-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of serum concentration of IL-6 and TNFα in systemic lupus erythematosus and rheumatoid arthritis: a candidate gene analysis

Abstract: Elevated concentrations of inflammatory mediators are characteristic of autoimmune disease accompanied by chronic or recurrent inflammation. We examined the hypothesis that mediators of inflammation known to be elevated in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) are associated with genetic polymorphism previously identified in studies of inflammatory disease. Serum interleukin 6 (IL-6) and tumor necrosis factor alpha (TNFα concentrations in patients with SLE (n=117) or RA (n=164) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…In reverse, PTPN2 is an important inhibitor of the secretion of proinflammatory cytokines like TNF. This has been confirmed by detecting significantly higher TNF levels in PTPN2-deficient mice [30,31] . We have previously shown that the presence of the PTPN2 SNP rs1893217 causes a diminished function of PTPN2 protein [4] .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In reverse, PTPN2 is an important inhibitor of the secretion of proinflammatory cytokines like TNF. This has been confirmed by detecting significantly higher TNF levels in PTPN2-deficient mice [30,31] . We have previously shown that the presence of the PTPN2 SNP rs1893217 causes a diminished function of PTPN2 protein [4] .…”
Section: Discussionsupporting
confidence: 66%
“…In that way, the inhibitory signals for TNF in the negative feedback loop are weakened and consequently more TNF is released. TNF reaches higher serum levels in patients with autoimmune diseases and is an essential pro-inflammatory cytokine that maintains chronic inflammation [31][32][33] . By blocking the excessive TNF production with anti-TNF agents, this viscous inflammation-maintaining cycle can be interrupted.…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, the disease manifests as sustained synovitis and erosion of articular cartilage and surrounding bone. Some proinflammatory cytokines, such as TNFα, interleukin 1B (IL‐1b), and IL‐6, are closely related to the incidence of RA …”
Section: Introduction Of Lncrnasmentioning
confidence: 51%
“…Some proinflammatory cytokines, such as TNFα, interleukin 1B (IL-1b), and IL-6, are closely related to the incidence of RA. [74][75][76] Müller et al analyzed lncRNA transcription in a microarray-based experiment of CD14(+) monocytes isolated from peripheral blood cells of RA patients before and after anti-IL-6R (tocilizumab) or anti-TNF-α (adalimumab) therapy. These researchers found that the expression of 7419 lncRNAs was changed by either IL-6 or TNF-α, and 85 of these lncRNAs exhibited significantly altered expression.…”
Section: Lncrnas and Human Autoimmune Diseasesmentioning
confidence: 99%
“…Serum levels of IL‐6 are significantly higher in SLE patients than in HCs . IL‐6 favors development of Tfh cells.…”
Section: Discussionmentioning
confidence: 96%